PENGARUH PEMBERIAN SIMETIDIN TERHADAP KADAR SGOT DAN SGPT TIKUS PUTIH (Rattus norvegicus) YANG DIBERI ANTI TUBERKULOSIS RIFAMPISIN DAN ISONIAZID - Siswandari, Wahyu; Pribadi, Fajar Wahyu; Perdini, Eska (MANDALA of Health, 2010)
Tuberkulosis (TB) has long been known as an infection diseases, and has been reported to increased.The INH dan Rifampisin are two different drugs that are known tobe the most active drugs, therefore bothdrugs are being used as never ending drugs in curing the TB. Utilization of both INH and rifampisin in acombination to cure the TB patients, however could increase the possibility of hepar lession risk. Thisresearch was aimed to firstly, knowing whether cimetidine could prevent increase of SGOT and SGPT levelsof rats (Rattus norvegicus) given by both drugs INH and rifampisin, and secondly what was the minimumdose of cimetidine that able to prevent the increase of SGOT and SGPT levels. A Completely Random Design(CRD) was applied in this research, 24 male rats (Rattus norvegicus) of the wistar variety were divided into4 different groups. The first group, was only given the INH and rifampisin orally at the doses of 50 mg/Kgbody weight/day, the next groups groups II, III, and IV were also given those two drugs at the same dose, butthe cimetidine was also given at 112,5 , 225, and 450 mg/Kg body weight/day for the 28 days. Consequentlythe SGOT and SGPT levels were measured twice pre and post treatments. The data obtained were analysiedby the paired t test, a one way ANOVA, Post Hoc Tukeyâs HSD, Kruskal-Wallis and Mann-Whitney test. Thisresearch result showed that the cimetidine that given following the INH and rifampisin could prevent theincrease of SGOT and SGPT levels. The highest dose of 450 mg/Kg body weight/day that given orally showedhighly significant different from other (p<0,00) in preventing the SGOT and SGPT of treated animals